2014
DOI: 10.1021/jf404827s
|View full text |Cite
|
Sign up to set email alerts
|

Production of Monoclonal Antibody for Okadaic Acid and Its Utilization in an Ultrasensitive Enzyme-Linked Immunosorbent Assay and One-Step Immunochromatographic Strip

Abstract: Okadaic acid (OA) is a common marine biotoxin that accumulates in bivalves and causes diarrhetic shellfish poisoning (DSP). This study generated a monoclonal antibody (mAb) specific to OA from a hybridoma cell line, 6B1A3, which was obtained by fusion of myeloma cells (P3/NS1/1-AG4-1) with spleen cells isolated from a BALB/c mouse immunized with OA-γ-globulin. The 6B1A3 mAb belongs to the immunoglobulin G1 (κ chain) isotype. Both competitive direct and indirect enzyme-linked immunosorbent assays (ELISAs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…For conjugation, AFB1 mAbs were dialyzed in boric acid-borax buffer (pH 8) for 24 h at 4 C and the gold nanoparticle solution was adjusted to pH 8.0 with 0.1 M K 2 CO 3 (pH 11.5) (Liu et al, 2013;Liu et al, 2014). Five mL of anti-AFB1A mAb (1 mg/ml) was added dropwise to 2 ml of gold nanoparticle solution with gentle stirring.…”
Section: Preparation Of Antibody-gold Nanoparticle Probementioning
confidence: 99%
See 2 more Smart Citations
“…For conjugation, AFB1 mAbs were dialyzed in boric acid-borax buffer (pH 8) for 24 h at 4 C and the gold nanoparticle solution was adjusted to pH 8.0 with 0.1 M K 2 CO 3 (pH 11.5) (Liu et al, 2013;Liu et al, 2014). Five mL of anti-AFB1A mAb (1 mg/ml) was added dropwise to 2 ml of gold nanoparticle solution with gentle stirring.…”
Section: Preparation Of Antibody-gold Nanoparticle Probementioning
confidence: 99%
“…Gold nanoparticles are conjugated with antibody as a tracer that provides a rapid visual evidence of the result (Liu, Hsu, Lu, & Yu, 2013;Liu, Hung, Lu, Chou, & Yu, 2014;Liu, Tsao, Wang, & Yu, 2008;Shim et al, 2007;Xiulan, Xiaolian, Jian, Zhou, & Chu, 2005). During the immunostrip assay, interaction occurs when test samples co-migrate with the antibody-gold nanoparticles that are conjugated along the strip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Liu et al. () found that levels of ADIPOR2 mRNA are increased in the liver after 48 h of fasting. Liu et al.…”
Section: Discussionmentioning
confidence: 97%
“…Gold nanoparticles were applied in immunostrip which is a promising immunoassay method to detect small molecular weight compound (Liu, Hung, Lu, Chou, & Yu, ; Shiu, Wang, & Yu, ; Xie et al, ). The principle of immunostrip relies on the movement of gold nanoparticle‐antibody conjugates and test sample along membrane strips on which the binding interactions occur.…”
Section: Introductionmentioning
confidence: 99%